Assessing carrying capacity under urban pressure in Pasaran Island, Bandar Lampung City, Indonesia - Nabilah, Rizka; Effendi, Hefni; Santoso, Nyoto; Sulistyantara, Bambang (Journal of Degraded and Mining Lands Management, 2025)
Rapid population growth in Bandar Lampung, especially in coastal areas, has impacted the environment. Pasaran Island is a small inhabited island that originally only had an area of 2 ha but has now grown to 12.02 ha due to sedimentation and reclamation carried out by the island's residents. Pasaran Island faces great challenges, especially related to carrying capacity and capacity to maintain environmental sustainability and the quality of life of its residents. This study aimed to analyze the carrying capacity and capacity of Pasaran Island. A spatial analysis approach was used to evaluate land requirements and the limits of the island's ability to support its population optimally. Spatial calculations used were according to the Regulation of the Minister of Public Works No.20/PRT/M/2007 on techniques for analyzing physical, environmental, economic, and socio-cultural aspects in preparing spatial plans. The results showed that the carrying capacity on the Pasaran Island is 0.601, which means that the carrying capacity of the settlement is low and unable to accommodate the population in the area. Based on the analysis of the carrying capacity of people, when viewed specifically on Pasaran Island, it can only accommodate 827 people, even though there are currently 1,500 residents. Thus, the results show that there is an overpopulation of 673 people.